The National Guard, the National Board for the Promotion of Rifle Practice, and the National Rifle Association: Public Institutions and the Rise of a Lobby for Private Gun Ownership - Marlin, Jeffrey A (2013)
Today, the strength of the National Rifle Association (NRA) is understood by the general public and many scholars to be dependent on the Second Amendment of the U.S. Constitution, the right of individuals to own firearms. This dissertation challenges that understanding by focusing on three organizations, the NRA, the National Guard and the National Board for the Promotion of Rifle Practice (NBPRP). While each organization appears in today's world to be distinct and independent, this dissertation reveals how they garnered strength from a symbiotic relationship. The NRA was founded in 1871, originally as a marksmanship organization. The National Guard, which grew from the nation's militia, was formally established in the early twentieth century. The NBPRP was a small organization that was established in 1903 within the War Department at the encouragement of the NRA. Following passage in 1903 of legislation bringing state militia units under federal control, the newly formed National Guard became dependent on the NRA, which in turn leveraged that dependence to create a nationwide grassroots organization. The NBPRP was headed by the Assistant Secretary of War until 1916 when the position of the Director of Civilian Marksmanship was created, to be held by a U.S. Army or U.S. Marine Corps officer. The NRA acted as the surrogate of the NBPRB outside of the halls of government. At the same time, the NBRPB provided the NRA with a voice within those same halls that aided in the development of federal policy and budget positions related to firearms acquisition, competition, and training. The purpose of this dissertation is to reveal how the NRA was able to employ these two organizations to develop an exceptionally powerful grassroots organization that today is recognized as one of the most powerful special interest groups in America. Understanding how this powerful organization grew offers one perspective of how the bureaucracy that has been developed to support America's federal system of government is uniquely susceptible to special interest influence